Methods and Tools for Urban Energy Planning. - Dall’O’, Giuliano; Ferrari, Simone (Springer, 2020)
Cities are responsible for around 70% of global energy demand and are considered as having a crucial role in effective abatement of global energy consumptions. The topic is largely discussed in available literature, which reveals the great diversity of applied approaches and the necessity to move towards the concept of smart energy systems, focussing on synergies among different energy sectors. However, considering the large share of responsibility of the building sector, this chapter focussed on related energy demand assessment. After an initial introduction, which spotlights the most complex elements, the chapter presents some methods of analysis to evaluate the energy performance of the existing building stocks. Subsequently an overview is presented of the methods and tools for determining the energy demand of buildings within urban energy planning, paying particular attention to those that rely on hourly profiles. The assessment of hourly energy demand of the existing building stock, as well as the prediction of its variation due to energy efficiency measures, are fundamental activities for planning strategies of distributed generation, district heating and/or cooling networks, renewables integration, energy storages, etc., all necessary in moving towards smart energy districts.
Keywords: Energieversorgung; Energiesystem; Urbaner Raum; Energieverbrauch; Gebäudebestand; Energiebedarf; Gebäudealter; Wärmebedarf; Heizung; Klimaanlage; Energieausweis; Energiesparen; Smart Energy